2013
DOI: 10.1007/s10995-013-1320-z
|View full text |Cite
|
Sign up to set email alerts
|

Parental Pregnancy Wantedness and Child Social-Emotional Development

Abstract: Objective To examine how maternal and paternal pregnancy wantedness and couple concordance regarding pregnancy wantedness predict children's socioemotional development in kindergarten. Methods We used data from nationally representative US sample from the Early Childhood Longitudinal Study Birth Cohort. Exposures of interest were maternal and paternal pregnancy wantedness, and couple concordance regarding wantedness. Children's socioemotional development was evaluated by the child's kindergarten teacher usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 27 publications
1
23
0
3
Order By: Relevance
“…93 The degree to which a pregnancy is wanted is associated with indicators of child well-being, 91,94,95 and child socioemotional development. 96 Thus, discussions in primary or other care visits regarding future pregnancies and contraceptive needs can help ensure the well-being of future generations. For clinicians who care for adolescents and parents of childbearing age, these discussions include desire for current and future pregnancy, impact of a potential pregnancy on social and economic circumstances, planning for future pregnancy, contraception counseling, vitamins with folate for all women of childbearing age, and counseling on healthy behaviors for potential future pregnancies.…”
Section: Reproductive Life Planningmentioning
confidence: 99%
“…93 The degree to which a pregnancy is wanted is associated with indicators of child well-being, 91,94,95 and child socioemotional development. 96 Thus, discussions in primary or other care visits regarding future pregnancies and contraceptive needs can help ensure the well-being of future generations. For clinicians who care for adolescents and parents of childbearing age, these discussions include desire for current and future pregnancy, impact of a potential pregnancy on social and economic circumstances, planning for future pregnancy, contraception counseling, vitamins with folate for all women of childbearing age, and counseling on healthy behaviors for potential future pregnancies.…”
Section: Reproductive Life Planningmentioning
confidence: 99%
“…Carson et al [30] found that children born of unintended pregnancies have lower verbal skills at 3 or 5 years of age than their planned or arti cially conceived counterparts, however this difference was explained by socioeconomic inequalities. In kindergarten, these children show lower social-emotional development [15]. Our results show signi cantly lower language skills already at 12 months of corrected age, as well as signi cantly lower cognitive skills.…”
Section: Pregnancy Planningmentioning
confidence: 46%
“…Secondary prevention interventions could include targeted parental support interventions to at-risk families. Studies have shown that mothers' retrospective perceptions of pregnancy desire can be predictive for the child's social-emotional development [24]. In the post-partum period, information on the child being wanted could be gathered by health-care personnel to guide them on where to focus resources.…”
Section: Future Interventions and Researchmentioning
confidence: 99%